Answer:
B
Explanation:
Given the 2 equations
y = 2x² - 5x - 7 → (1)
y = 2x + 2 → (2)
Since both equations express y in terms of x we can equate the right sides, that is
2x² - 5x - 7 = 2x + 2 ( subtract 2x + 2 from both sides )
2x² - 7x - 9 = 0 ← in standard form
Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term
product = 2 × - 9 = - 18 and sum = - 7
The factors are + 2 and - 9
Use these factors to split the x- term
2x² + 2x - 9x - 9 = 0 ( factor the first/second and third/fourth terms )
2x(x + 1) - 9(x + 1) = 0 ← factor out (x + 1) from each term
(x + 1)(2x - 9) = 0
Equate each factor to zero and solve for x
x + 1 = 0 ⇒ x = - 1
2x - 9 = 0 ⇒ 2x = 9 ⇒ x = 4.5
Substitute these values into (2) for corresponding values of y
x = - 1 : y = (2 × - 1) + 2 = - 2 + 2 = 0 ⇒ (- 1, 0)
x = 4.5 : y = (2 × 4.5) + 2 = 9 + 2 = 11 ⇒ (4.5, 11)
Solutions are (4.5, 11) and (- 1, 0)